Glow Discharge in a High-Velocity Air Flow: The Role of the Associative Ionization Reactions Involving Excited Atoms - Cejas, Ezequiel (2019)
A kinetic scheme for non-equilibrium regimes of atmospheric pressure air discharges is developed. A distinctive feature of this model is that it includes associative ionization with the participation of N(2D, 2P) atoms. The thermal dissociation of vibrationally excited nitrogen molecules and the electronic excitation from all the vibrational levels of the nitrogen molecules are also accounted for. The model is used to simulate the parameters of a glow discharge ignited in a fast longitudinal flow of preheated (T0 = 1800-2900 K) air. The results adequately describe the dependence of the electric field in the glow discharge on the initial gas temperature. For T0 = 1800 K, a substantial acceleration in the ionization kinetics of the discharge is found at current densities larger than 3 A/cm2, mainly due to the N(2P) + O(3P)→NO+ + e process; being the N(2P) atoms produced via quenching of N2(A3∑u+) molecules by N(4S) atoms. Correspondingly, the reduced electric field noticeably falls because the electron energy (6.2 eV) required for the excitation of the N2(A3∑u+ state is considerably lower than the ionization energy (9.27 eV) of the NO molecules. For higher values of T0, the associative ionization N(2D) + O(3P) → NO+ + e process (with a low-activation barrier of 0.38 eV) becomes also important in the production of charged particles. The N(2D) atoms being mainly produced via quenching of N2(A3∑u+ molecules by O(3P) atoms.